2007
DOI: 10.1111/j.1447-0756.2007.00533.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the use of electrothermal bipolar vessel sealer with harmonic scalpel in total laparoscopic hysterectomy

Abstract: EBVS was found to be less time-consuming and caused less bleeding when compared with HS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 21 publications
5
28
0
2
Order By: Relevance
“…According to these data, LVSS causes less tissue damage than HS and electrocautery on the lung. LVSS produces a significantly reduced thermal spread, as the energy is automatically switched off when the tissue impedance reaches a critical level [2] , thus leading to a lung-tissue-preserving effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to these data, LVSS causes less tissue damage than HS and electrocautery on the lung. LVSS produces a significantly reduced thermal spread, as the energy is automatically switched off when the tissue impedance reaches a critical level [2] , thus leading to a lung-tissue-preserving effect.…”
Section: Discussionmentioning
confidence: 99%
“…LVSS has mainly been used for vessel sealing as an alternative to sutures, hemoclips, staplers and ultrasonic coagulators. LVSS seals the vessel up to 7 mm in diameter and had been used in abdominal surgery [2][3][4] . Lacin et al [19] used LVSS in an experimental study and revealed that segmental branches of pulmonary arteries and veins could be sealed safely with LVSS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, EBVS systems are offered by various manufacturers and widely used in several surgical specialties such as general and visceral surgery [1,3,4], gynecology [5,6], urology [2,7], cardio-thoracic [8], and pediatric surgery [7,9]. Recent systematic reviews and meta-analyses of randomized controlled clinical trials [10-12] revealed that EBVS systems are safe and at least equally effective concerning blood loss and operating time in comparison to ultrasonic energy devices for blood vessel transection in abdominal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Pour le temps d'hystérectomie laparoscopique, l'utilisation de dispositifs intégrés permettant de coaguler et sectionner les vaisseaux est un réel progrès. Notre préférence va au système LigaSure 1 (Covidien) [31], mais l'utilisation des ultrasons par Ultracision 1 (Ethicon) est également efficace. La pose de clips sur l'origine de l'artère utérine, à la fin de la lymphadénectomie diminue encore les pertes sanguines, tout en réduisant quelque peu, par ischémie, la taille de l'utérus [32].…”
Section: L'obésitéunclassified